"Is it Language or Disability?": An Ableist and Monolingual Filter for English Learners with Disabilities. Issue 3 (24th October 2021) - Kangas, Sara E.N.
Abstract : In United States K‐12 schools, the question "Is it language or disability?" is one often asked about students dually identified as English learners (ELs) and students with disabilities . In this article, the author provides a brief historical overview of how and why this question arose in educational praxis. The author then explores the ways in which the question has evolved into a pervasive and troubling filter through which educators attempt to make sense of the academic performance, linguistic development, and even behaviors of ELs with disabilities. This language‐or‐disability filter, however, as the author argues, inordinately focuses on language and disability alone while ignoring the systemic contributors to the academic difficulties ELs with disabilities encounter. By attributing disability or language as the sole source of a wide range of "problems, " the filter reinforces a deficit mindset rooted in ableism and monolingualism. The author concludes the article by offering alternatives to "Is it language or disability?" that account for and shift attention to the systemic disadvantage ELs with disabilities experience in their schooling.